Reliability of the Charcot‐Marie‐Tooth functional outcome measure. Issue 3 (26th August 2020) - Bray, Paula; Cornett, Kayla M. D.; Estilow, Timothy; Pareyson, Davide; Zuccarino, Riccardo; Skorupinska, Mariola; Pipis, Menelaos; Sowden, Janet E.; Scherer, Steven; Reilly, Mary M.; Shy, Michael E.; Herrmann, David N.; et al.
Abstract: The CMT‐FOM is a 13‐item clinical outcome assessment (COA) that measures physical ability in adults with Charcot‐Marie‐Tooth disease (CMT). Test‐retest reliability, internal consistency and convergent validity have been established for the CMT‐FOM. This current study sought to establish inter‐rater reliability. Following an in‐person training of six international clinical evaluators we recruited 10 participants with genetically diagnosed CMT1A, (aged 18‐74 years, 6 female). Participants were evaluated using the CMT‐FOM over 2 days. Participants were given at least a 3 hour rest between evaluations, and were assessed twice each day. Following the provision of training by master trainers, all 13 items of the CMT‐FOM exhibited excellent inter‐rater reliability for raw scores (ICC1, 1 0.825‐0.989) and z‐scores (ICC1, 1 0.762‐0.969). Reliability of the CMT‐FOM total score was excellent (ICC1, 1 0.983, 95% CI 0.958‐0.995). The CMT‐FOM is a reliable COA used by clinical evaluators internationally. The next steps are to establish further validation through psychometric evaluation of the CMT‐FOM in the Accelerate Clinical Trials in CMT (ACT‐CMT) study.